Development of physical activity of higher educational institutions students in the process of recreational kayaking outdoor classes - Shevchuk, Andrii (Journal of Education, Health and Sport, 2017)
The article substantiates the method of recreational kayaking classes. Implementation of the developed methodology was carried out during the studying year with the change to individual classes during the vacation period. The proposed methodology included theoretical and practical material, as well as the means of medical and pedagogical control. It foresees a phased (including adaptation mechanisms) expansion and increase in the intensity of physical activity in outdoor forms of students’ sports and mass exercises.